2005
DOI: 10.1055/s-2005-861054
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Biliary Drainage by Nasobiliary Drain or by Stent Placement in Patients with Acute Cholangitis

Abstract: Biliary drainage by nasobiliary drain and drainage by stent are equally safe and effective treatments for patients with severe cholangitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 17 publications
2
80
0
5
Order By: Relevance
“…Theoretically, a large stent offers better drainage and a lower rate of stent occlusion than a small stent. However, previous studies showed no significant stent occlusion for both a 10 FR stent and a 6-7 FR stent (27,28). The other reasons considered in selecting 7 and 8.5 FR stents were easy operation and reduced trauma to the bile duct, particularly for elderly, fragile patients.…”
Section: Original Articlementioning
confidence: 99%
“…Theoretically, a large stent offers better drainage and a lower rate of stent occlusion than a small stent. However, previous studies showed no significant stent occlusion for both a 10 FR stent and a 6-7 FR stent (27,28). The other reasons considered in selecting 7 and 8.5 FR stents were easy operation and reduced trauma to the bile duct, particularly for elderly, fragile patients.…”
Section: Original Articlementioning
confidence: 99%
“…Generation (hier vor allem das Ceftriaxon). Ist die Cholezystitis begleitet von einer Cholangitis, wird eine Entlastung des Gallengangsystems mittels endoskopischer retrograder Cholangiopankreatographie empfohlen [20].…”
Section: Who-stufe-3-medikamenteunclassified
“…It is widely recognized that endoscopic biliary drainage (EBD) [1][2][3] in patients with acute cholangitis is important as the initial treatment. EBD and treatment of the papilla of Vater, which includes endoscopic sphincterotomy (EST) [4] and endoscopic papillary balloon dilation (EPBD) [5], are required for patients with acute cholangitis associated with choledocholithiasis, but these modalities are not yet aggressively applied as the initial treatment since cholangitis has been regarded as a risk factor for post-EST hemorrhage [6].…”
Section: Introductionmentioning
confidence: 99%